2022
DOI: 10.1038/s41420-022-01087-1
|View full text |Cite
|
Sign up to set email alerts
|

Promising prognostic value of Transglutaminase type 2 and its correlation with tumor-infiltrating immune cells in skin cutaneous melanoma

Abstract: Tissue Transglutaminases (TGs) are crosslinking enzymes with pleiotropic functions that have been linked to the development and progression of numerous cancers, with a recent focus on their ability to remodel the tumor microenvironment. Although several pieces of evidence demonstrated their importance in the regulation of the major signaling pathways that control oncogenesis, the correlation between TGs with clinical and pathological features remains controversial and to be further explored. Moreover, an asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 68 publications
1
4
0
1
Order By: Relevance
“…1g ). These results are in line with our previous research in which we outlined a novel promising positive clinical value for TG2 in skin cancer [ 21 ], though the molecular mechanism behind TG2 function was not fully elucidated.
Fig.
…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…1g ). These results are in line with our previous research in which we outlined a novel promising positive clinical value for TG2 in skin cancer [ 21 ], though the molecular mechanism behind TG2 function was not fully elucidated.
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…Still, the part played by TG2 in EMT processes has already been highlighted in several contexts [ 20 ]. To shed light on the controversies regarding its role in cancer disease, we performed bioinformatics analyses on public cancer datasets which unveiled that the prognostic role of TG2 is generally negative, except for SKCM, the only tumor type in which TG2 expression is associated with a positive prognosis, as we already mentioned in Muccioli et al, 2022 [ 21 ]. In the same article, we reported that TG2 expression was upregulated in metastatic samples compared to primary tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TG2 expression was previously reported to be altered in several tumors [ 17 , 26 , 41 , 42 , 43 ]. An investigation of TG2 expression levels in patients affected by different types of cancers was conducted using the publicly available GEPIA (Gene Expression Profiling Interactive Analysis) database [ 27 ].…”
Section: Tg2 In Cancermentioning
confidence: 99%
“…Thus, TG2 KO melanoma cells are less differentiated, unable to pigment, and form larger metastases when injected in vivo [ 57 ]. Moreover, TG2 is a positive prognostic factor as its knock-out (KO) seems to be correlated with the impairment of the immune cell recruitment and activation [ 43 ].…”
Section: Tg2 In Cancermentioning
confidence: 99%